2010
DOI: 10.1111/j.1468-5957.2010.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Target Price Accuracy in Equity Research

Abstract: target prices , analyst recommendation , security analysis ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Two seminal papers (Brav andLehavy 2003, Asquith, Mikhail, andAu 2005) have shown that target prices contain relevant information for capital markets, even conditionally on other information that is issued in the form of, for example, earnings price forecasts. With respect to the question of target price accuracy, evidence is still evolving with a number of (working) papers (e.g., Bonini, Zanetti, Bianchini, and Salvi 2010, Bradshaw and Brown 2006, Gleason, Johnson, and Li 2008. We contribute to the literature by analyzing target price accuracy in the German capital market.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Two seminal papers (Brav andLehavy 2003, Asquith, Mikhail, andAu 2005) have shown that target prices contain relevant information for capital markets, even conditionally on other information that is issued in the form of, for example, earnings price forecasts. With respect to the question of target price accuracy, evidence is still evolving with a number of (working) papers (e.g., Bonini, Zanetti, Bianchini, and Salvi 2010, Bradshaw and Brown 2006, Gleason, Johnson, and Li 2008. We contribute to the literature by analyzing target price accuracy in the German capital market.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Cooper, Day, and Lewis (2001) and Bernhardt, Campello, and Kutsoati (2004) showed that published compensation schedules by banks include earnings forecast accuracy but not target price accuracy as a factor for setting analysts' salaries. Bonini, Zanetti, Bianchini, and Salvi (2010) additionally argued that target prices might be subject to biases since there is no explicit control of the forecast quality. Hence, analysts might use target prices strategically, e.g., in order to increase the sales hype of a stock (e.g., Asquith, Mikhail, and Au 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Target prices are not a measure of a company's fair value but are actually measures of the fair value subjectively adjusted by each analyst for exogenous factors such as market momentum, liquidity or industry factors. As such, we believe that target prices are the optimal instrument to test the information revelation by equity analysts In particular we measure the information content of target prices by computing their accuracy given by the degree of proximity of the share price to the target following the methodology developed in Bonini et al (2010) This approach identi…es two metrics 2 and 4 capturing respectively: the proximity of the share price to the target at any point in time over the prediction window of the target and the proximity of the share price to the target at the end of the forecast windows. Formally we compute:…”
Section: Equity Analyst Accuracy and The Reputation Sentiment Indexmentioning
confidence: 99%